An outbreak of dermatophilosis in a dairy cattle farm in the area of Thessaloniki. - GIADINIS (Ν. ΓΙΑΔΙΝΗΣ), N.; SARIDOMICHELAKIS (Μ.Ν. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ), M. N.; KOUTINAS (Α. Φ. ΚΟΥΤΙΝΑΣ), A. F.; KARATZIAS (Χ. ΚΑΡΑΤΖΙΑΣ), H. (Journal of the Hellenic Veterinary Medical Society, 2018)
A retrospective study of an outbreak of dermatophilosis in a dairy cattle farm of 40 cows, 12 heifers, 15 bullocks and 10 newborn calves, in the area of Thessaloniki, is presented. To our knowledge this is the first time such an outbreak has been reported in Greece. In 62 of the 77 animals (80.5%) the characteristic skin lesions of the chronic form of the disease were found. None of the bullocks, which did not have access to the open yard, were clinically affected. The disease first appeared in the farm soon after a tractor had been used to dispose the manure from the yard. The mildly painful lesions, involving various parts of the hairy and glabrous skin, were characterized by dry and thick crusts, erythema, hyperpigmentation, erosions and alopecia. Due to the chronic nature of the disease, diagnosis was based on the clinical appearance and skin histopathology, where the organisms were demonstrated with difficulty within the keratin of the crusts, appearing as chains of two parallel rows of coccoid cells. Clinical resolution occurred within a few weeks after one injection of long-acting Oxytetracycline. No recurrence of the disease has ever been reported. Despite the zoonotic potential of dermatophilosis, none of the people who had been in contact with the infected cattle developed skin lesions.